Unit operations for the production of dark, milk, and white chocolate. A systematic review - Villafuerte-Carrillo, Franklin Rolando; Sancho Aguilera, David; Enríquez-Estrella, Miguel Ángel; Basantes-Basantes, Edwin Fernando; Ruíz-Mármol, Hernán Patricio (Revista Colombiana de Investigaciones Agroindustriales, 2024)
The chocolate production process involves several critical stages with specific operating ranges; therefore, this article aimed to analyze the unit operations for the production of dark, milk, and white chocolate through a systematic review. The study followed PRISMA guidelines, applying eligibility and exclusion criteria for selecting scientific articles, theses, books, and standards. This allowed for the final inclusion of 78 studies out of a total of 396 selected for review. The research focused on the process of searching and selecting documents based on inclusion criteria, covering the stages from the reception of fermented and dried cocoa beans to the storage of the final product. The main findings included: A) the chocolate production process with several crucial stages, such as: reception of the cocoa bean with a moisture content of 6 % – 8 %; roasting at temperatures between 110 °C - 160 °C for 5 to 120 minutes, which contributes to the development of the characteristic chocolate flavor; alkalization raises the pH from 5.2 to 7.5, reducing the product's acidity; refining the chocolate mass to obtain a particle size of 15-35 microns at temperatures between 45 °C to 70 °C; conching the chocolate mass at 60 °C - 90 °C for 6 to 20 hours, which improves the texture and flavor profile of the chocolate; tempering the chocolate with a specific temperature profile for each type of chocolate (e.g., for milk chocolate: 50 °C → 32 °C → 27 °C → 30 °C - 32 °C), which is essential for achieving the proper crystallization of cocoa butter, affecting the texture and appearance of the final tablet product; and ending with chocolate storage at temperatures below 20 °C. Each type of chocolate (dark, milk, and white) has variations in its production process and composition. In conclusion, working ranges are crucial to achieving the desired sensory and quality characteristics in the final product and may vary depending on the specific type of chocolate being produced.